L2 WRITING STRATEGIES USED BY HIGH SCHOOL STUDENTS - Syaadiah Arifin (PROJECT (Professional Journal of English Education), 2020)
Writing is a challenging activity that comprises a complex cognitive process, as well as various strategies. Furthermore, minimal research has been performed on using writing strategies among High School students in the EFL context, specifically in Indonesia. Although the applications of effective strategies have been evidenced to be helpful, many students are not aware of using them to alleviate their writing quality. Therefore, this study aims at investigating English L2 strategies when writing recount texts using three skilled English students. This is a qualitative research that utilized purposive sampling and the instruments employed were Think-Aloud Protocols (TAPs), observation, retrospective, and semi-structured interviews. Following the analysis and interpretation of the data obtained from these instruments, the acquired results demonstrated that they used similar writing strategies. However, the occurrences from this use differed from one individual to another as some were unaware that the writing process was recursive and not linear. Therefore, this study implies that students need to be encouraged to apply different strategies to develop their writing, and teachers also, were required to explicitly teach these strategies as it will lead students to use them effectively. Training on the use of writing strategies is needed for Indonesian students to support and help them write efficiently in English.